2017
DOI: 10.3390/nu9111185
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Micronutrient Status in Critically Ill Children: Challenges and Opportunities

Abstract: Micronutrients refer to a group of organic vitamins and inorganic trace elements that serve many functions in metabolism. Assessment of micronutrient status in critically ill children is challenging due to many complicating factors, such as evolving metabolic demands, immature organ function, and varying methods of feeding that affect nutritional dietary intake. Determination of micronutrient status, especially in children, usually relies on a combination of biomarkers, with only a few having been established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 215 publications
(297 reference statements)
1
65
1
8
Order By: Relevance
“…Plasma zinc is a good indicator of zinc intake in the absence of systemic inflammation [10]. In the present study, low serum levels of Zn were observed in 76% of patients at the time of ICU admission.…”
Section: Discussionsupporting
confidence: 45%
“…Plasma zinc is a good indicator of zinc intake in the absence of systemic inflammation [10]. In the present study, low serum levels of Zn were observed in 76% of patients at the time of ICU admission.…”
Section: Discussionsupporting
confidence: 45%
“…Согласно результатам не-скольких исследований, применение препаратов цинка внутрь способствует сокращению продолжительности тяжелой пневмонии у детей (табл. 1) [15,37].…”
Section: препараты цинкаunclassified
“…Although obesity in children may lead to vitamin B-12 deficiency, the dietary assessment of obese patients before admission in addition to laboratory assessments should be considered in PICUs (49). Some studies reported that high vitamin B-12 level is associated with high inflammation and mortality rate in critically ill adult patients (50). More studies are needed to identify the state of vitamin B-12 in critically ill obese children.…”
Section: Micronutrient Requirementmentioning
confidence: 99%
“…Most critically ill patients are at the increased risk of vitamin A deficiency development according to their nutrition and metabolic states. The deficiency can be severe in patients with lower hepatic retinol storage that probably occurs in obese patients due to recent dietary restrictions for weight reduction such as skimmed dairy products and eggs as two of the best sources of retinol (50).…”
Section: Micronutrient Requirementmentioning
confidence: 99%